ANALISIS ASPEK YURIDIS KEBIJAKAN RESTRUKTURISASI KREDIT DALAM MASA PANDEMI CORONAVIRUS DISEASE 2019 PADA USAHA MIKRO, KECIL, DAN MENENGAH DI PT. BPR SURYA UTAMA SUKOHARJO - Putri Indrawati Utama; Pranoto Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2025)
This article aims to analyze the juridical aspect nof credit restructuring as attempt of saving non perfoming loan due to Covid-19 in the implementation of credit restructuring in PT. BPR Surya Utama Sukoharjo. This research method is empirical legal research with a qualitative approach. The legal materials used are primary legal materials and secondary legal materials. The technique of collecting data by interviews with employees of PT. BPR Surya Utama Sukoharjo. Data analysis by means of data collection, data reduction, data presentation, data verification and drawing conclusions. The result of research shows that PT. BPR Surya Utama Sukoharjo provides credit restructuring to UMKM debtors through several stages according to Peraturan Otoritas Jasa keuangan Nomor 48/POJK.03/2020. The policy provides justice and legal benefits but does not provide legal certainty. Because there are still uncertain clauses.